Kontribusi Permainan Tradisional Terhadap Karakter Keterbukaan Pikiran Anak Usia 10-12 Tahun - Widyati, Dwi Rahayuning; Nugrahanta, Gregorius Ari (Indonesian Journal of Educational Counseling, 2023)
The purpose of this researched was to develop a character education guidebook for open-mindedness based on traditional games for children aged 10-12 years. The problem statement of the researched was how to develop a traditional game-based character education guidebook, how was the quality of the guidebook, and did the guidebook affected the open-mindedness character of children. The researched model used was R & D typed ADDIE. The results of the studied explained that 1) the open-mindedness character education guidebook based on traditional games was developed used the ADDIE stages; 2) the quality of the character education guidebook got a score of 3.87 (range 1-4) which was classified in the category of "very good" and "no needed for revision"; and 3) application of open-minded character education guidebook based on traditional games affected children's open-minded character with the result of a significance test t= 9.815, p= 0.000 (p < 0.05). The product was included in the "big effect" with a valued of r = 0.9750170916 or equivalent to an effect of 95.1% and its effective valued was "high" with an N-Gain Score = 87.19%